Article Review : Analisis Kadar Merkuri pada Sediaan Kosmetik Menggunakan Metode Spektrofotometri Serapan Atom - Bilqisti Kanzabila Karim; Eri Amalia (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Mercury is a highly toxic and bioaccumulative heavy metal. Despite its prohibition, mercury is still frequently found as a contaminant in cosmetic products, particularly in whitening products. This article aims to review and present various findings from previous studies on mercury levels in cosmetic preparations marketed in Indonesia, analyzed using the Atomic Absorption Spectrophotometry (AAS). The method employed is a literature review of scientific articles published between 2015 and 2025, selected based on their focus on mercury analysis in cosmetics use of the AAS method. The review results show that the majority of whitening creams and lotions contain mercury levels exceeding the safety limits set by the Indonesian National Agency of Drug and Food Control (BPOM RI), with some samples showing extremely high concentrations reaching thousands of ppm. In contrast, other preparations such as powders, hair dyes, and deodorants generally have low or undetectable mercury levels. These findings indicate a lack of understanding regarding mercury and its dangers, especially regarding compliance with regulations on cosmetic products, especially those sold online. The conclusion of this review emphasizes the need for enhanced regulatory enforcement, stricter supervision, and increased public education to protect consumers from the health risks posed by mercury-containing cosmetics.